The bridging understanding of language and mathematical symbols between teachers and students: An effort to increase mathematical literacy - Imam Kusmaryono; Mohamad Aminudin; Nila Ubaidah; Evi Chamalah (IKIP Siliwangi and I-MES, 2024)
The research aims to analyze the gap between teachers' and students' understanding of language literacy and mathematical symbols. The study was designed with a concurrent triangulation strategy. The research respondents consisted of 20 teachers and 120 class VII students. Data collection through questionnaires, interviews, and cognitive tests. Qualitative data was analyzed descriptively, and quantitative data was analyzed inferentially. The results of the analysis of quantitative data show that there is a linear (significant) relationship between understanding language and mathematical symbols and mathematical literacy skills. The results of the qualitative data analysis describe that the teacher's understanding of language and mathematical symbols (high criterion) does not necessarily support the students' understanding of language and mathematical symbols. We confirm the suspicion that there is a gap in the ability of teachers and students to understand language and mathematical symbols. Students need to improve their understanding of mathematical language and symbols. The pattern of errors is based on the teacher's conception of learning in the previous class, so the process of transitioning the teacher's knowledge to students' understanding of mathematics experiences obstacles. The implication is that the process of transitioning meaning from mathematical symbols to written and spoken language must be carried out when the teacher introduces or teaches new topics to students, and the context in which mathematical symbols are used must be followed by clarification.